Chemotherapeutic Strategies for Combating Staphylococcus aureus Infections - Sharma, Namita; Chhillar, Anil K.; Dahiya, Sweety; Punia, Aruna; Choudhary, Pooja; Gulia, Prity; Behl, Akanksha; Dangi, Mehak (Mini Reviews in Medicinal Chemistry, 2022)
Abstract: Staphylococcus aureus is a prominent human pathogen that causes nosocomial and community acquired infections. The accelerating emergence and prevalence of staphylococcal infections have grotesque health consequences which are mostly due to its anomalous capability to acquire drug resistance and scarcity of novel classes of antibacterials. Many combating therapies are centered on primary targets of S. aureus which are cell envelope, ribosomes and nucleic acids. This review describes various chemotherapeutic strategies for combating S. aureus infections including monotherapy, combination drug therapy, phage endolysin therapy, lysostaphins and antibacterial drones. Monotherapy has dwindled in due course of time, but combination therapy, endolysin therapy, lysostaphin and antibacterial drones are emerging alternatives which efficiently conquer the shortcomings of monotherapy. Combinations of more than one antibiotic agents or combination of adjuvant with antibiotics provide a synergistic approach to combat infections causing pathogenic strains. Phage endolysin therapy and lysostaphin are also presented as possible alternatives to conventional antibiotic therapies. Antibacterial Drones go a step further by specifically targeting the virulence genes in bacteria, giving them a certain advantage over existing antibacterial strategies. But the challenge remains on the better understanding of these strategies for executing and implementing them in the health sector. In this day and age, most of the S. aureus strains are resistant to an ample number of antibiotics, so there is an urgent need to overcome such multidrug-resistant strains for the welfare of our community.
Keywords: antibiotics